Learning Thoracoscopic Lobectomy in Resident Training - Huang, Chang-Lun; Liu, Chia-Chuan; Cheng, Ching-Yuan; Lin, Ching-Hsiung; Wu, Yu-Chung; Wang, Bing-Yen (The Thoracic and Cardiovascular Surgeon, 2014)
Background Thoracoscopic lobectomy is a safe and effective procedure; however, the ways by which to incorporate this technically demanding procedure into residency training is still unknown. We reported on the outcomes of thoracoscopic lobectomies performed by a single thoracic resident, who was simultaneously undergoing training for both open and thoracoscopic lobectomies.Patients and Methods Between January 2010, and May 2011, data from 87 consecutive thoracoscopic lobectomies that were performed by a trainee surgeon (B.-Y.W.) were prospectively obtained. Data were grouped into the first 30 and subsequent 57 cases. Patient characteristics, operative data, complications, and surgical pathology were analyzed.Results The mean operating time in group 2 was significantly lower compared with group 1 (264.0 ± 45.9 min in group 1 vs. 197.5 ± 57.7 min in group 2; p < 0.001). There were no mortalities in both the groups and no significant differences in postoperative complications.Conclusions Thoracoscopic lobectomy can be taught to a nonexperienced thoracic resident during an open procedure without compromising the safety of patients. It appears that surgical performance reaches a plateau after the completion of 30 cases.
Keywords: thoracoscopic lobectomy; resident training; learning curve